Konsolidasi Militan Islam dan Reproduksi Makna Jihad - Chaider S. Bamualim (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
The Islamization that has swept the Islamic world in recent decades has successfully consolidated Islamic movements and reproduced the meaning of jihad, activating it as a controversial ideological instrument. This phenomenon inevitably often leads to misunderstandings, both among Muslims themselves and among non-Muslims in the West and the East. For some Western scholars, jihad, an Islamic teaching, is synonymous with religious war (holy war). Therefore, Islam is labeled as a brutal religion, applying militaristic patterns and declaring war not only permissible but also sacred. Islam—because of the doctrine of jihad—is also seen as promoting the use of violence to proselytize non-Muslims into Islam. Such misunderstandings have had fatal consequences and have unjustly portrayed Islam as a religion of violence and terrorism, as well as a threat to Western civilization. This portrayal has then perpetuated long-standing suspicions against the Muslim community.